Europa w kryzysie: perspektywy gospodarcze Unii Europejskiej do 2020 roku w kontekście problemów rozwojowych państw grupy PIIGS - Walkowski, Maciej (Wydawnictwo Naukowe WNPiD UAM, 2012)
In 2009 the European Union, and in particular the euro zone, slid into a stage of economic recession, on account of the spreading global financial crisis, referred to as ‘2008+.’ Considerable developmental problems are being experienced by the group of countries referred to as PIIGS, particularly by Greece. Due to the tight developmental interdependencies in the European common market, the bankruptcy of Greece could cause a domino effect, i.e. the collapse of other Mediterranean economies, such as Spain or Italy, financial difficulties for Germany and France, and consequently a threat to integration processes throughout Europe. This paper is the first part of the analysis of this issue, where the author analyzes both the causes and effects of the present financial crisis in the euro zone, the first correctional activities undertaken by the EU institutions, and further developmental prospects of the European Union by 2020.
Europe in crisis: economic prospects of the European Union by 2020 in the context of developmental problems in the PIIGS group
Keywords: Kryzys; Unia Europejska; Państwa grupy PIIGS